1976
DOI: 10.1111/j.1365-2265.1976.tb01960.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic‐pituitary Function Following Successful Treatment of Intracranial Tumours

Abstract: Hypothalamic-pituitary function was examined in seventeen patients treated in the past for extrasellar intracranial tumours. All patients had received a course of external cranial irradiation. Biochemical abnormalities of endocrine function were present in almost all of the patients. In particular, the growth hormone response to insulin induced hypoglycaemic stress was impaired in eleven out of fifteen patients. Preliminary data from a group of seven patients with intracranial tumours prior to radiotherapy are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

1982
1982
1994
1994

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 24 publications
0
13
0
2
Order By: Relevance
“…Endocrine complications following cranial irradiation were recognised over 20 years ago (Tan & Kunaratnam, 1966) but their degree is still emerging. GHI is known to be common (Harrop et al, 1976); we found that almost all children given cranial irradiation had GHI when assessed by ITT. The resultant failure of Shalet established that the dose of radiation received by the hypothalamopituitary axis was the determining factor for GHI but a critical dose has not been identified (Shalet et al, 1977b;Ahmed et al, 1986).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Endocrine complications following cranial irradiation were recognised over 20 years ago (Tan & Kunaratnam, 1966) but their degree is still emerging. GHI is known to be common (Harrop et al, 1976); we found that almost all children given cranial irradiation had GHI when assessed by ITT. The resultant failure of Shalet established that the dose of radiation received by the hypothalamopituitary axis was the determining factor for GHI but a critical dose has not been identified (Shalet et al, 1977b;Ahmed et al, 1986).…”
Section: Discussionmentioning
confidence: 64%
“…It has become clear, however, that the large numbers of children cured of their original tumour are at risk for longterm sequelae, mainly from the radiotherapy (Shalet et al, 1975;Harrop et al, 1976). Cranial irradiation may damage the hypothalamo-pituitary axis leading to growth hormone (GH) deficiency and other endocrine dysfunction.…”
mentioning
confidence: 99%
“…Apart from a reduction in the total amount of Gil secreted there was also a significant disturbance in the periodicity of Gil secretion in the irradiated (1,800 cGy) pubertal children (15); a finding which has also been observed in the first year after TBI for childhood leukemia (11). Cranial irradiation for treatment of a cranial tumor (2,20), tumors of eye and middle ear for a brain tumor (28). In 46 GH deficient children previously irradiated for a brain tumor not involving the hypothalamic-pituitary axis there was a significant linear association between age at irradiation and age at onset of puberty.…”
Section: Gh Testsmentioning
confidence: 80%
“…A análise de testes endócrinos dinâmicos tem fornecido informações de que o hipotálamo é mais sensível à radiação que a hipófise i, 9,12,15,17,23. Pacientes com tumor fora do eixo HH 9,12 e crianças leucémicas 6 não apresentam déficit na secreção do GH.…”
Section: Comentáriosunclassified
“…Semelhante observação em relação ao GH foi constatada em paciente com edema cerebral, ocasionado por cetoacidose diabética 13. A importância fisiológica da secreção do GH no adulto é pouco entendida 12,17 ? mas sua deficiência na criança ocasiona bloqueio no crescimento, qualquer que seja a doença básica para a qual foi dirigida a terapêutica 5,9,11,12,15,17,19,23 Em nossa casuística, dois pacientes (7 e 8) apresentaram comprometimento da secreção do TSH, enquanto um outro (3; tinha nível basal aumentado, mas com resposta normal ao estímulo. Estes dados sugerem que a secreção do TSH é aquela que por último e com menor frequência se compromete após tratamento dç tumores parasseiares, o que vem confirmar alegações de outros autores 17.…”
Section: Alguns Pacientes Em Coma Prolongado Podem Apresentar Respostunclassified